1997
DOI: 10.1086/514113
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Burden in Tissues and Cellular Compartments during Clinical Latency and AIDS

Abstract: In the course of human immunodeficiency virus infection or of the related simian immunodeficiency virus (SIV), progression to AIDS is associated with high virus burdens in blood. How virus burden in the bloodstream is related to virus burden in tissue reservoirs was addressed in an animal model of rhesus macaques infected with SIV. In situ hybridization and quantitative image analysis were used to quantitate virus burden. Animals who developed AIDS had high levels of virus production and storage in lymphoid ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 39 publications
1
53
1
Order By: Relevance
“…The decline in the CD4/CD8 ratio appeared unrelated to the occurrence of impairment on the different tasks ( Table 2) [42]. SIV-infected animals displayed an elevation in serum p26 antigen levels within 1 month of inoculation, although to variable degrees [42,43]. Elevated plasma viral load was associated with advanced disease (Table 2) but unrelated to the onset of impairments.…”
Section: Results With the Siv Modelmentioning
confidence: 98%
“…The decline in the CD4/CD8 ratio appeared unrelated to the occurrence of impairment on the different tasks ( Table 2) [42]. SIV-infected animals displayed an elevation in serum p26 antigen levels within 1 month of inoculation, although to variable degrees [42,43]. Elevated plasma viral load was associated with advanced disease (Table 2) but unrelated to the onset of impairments.…”
Section: Results With the Siv Modelmentioning
confidence: 98%
“…It makes sense that the lung becomes a site of infection as all blood passes through the lung to become oxygenated and thus lung tissue is highly vascularized. In some studies, the lung has been shown to be a place of active viral replication [45] [19]. Thus, the interaction with Mtb and HIV-1 in the lung may play a role in co-infection dynamics.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…We choose to model the dynamics of immune cells and pathogens in the lung as this is the primary site of infection for Mtb and there is evidence that the lungs are an important site for HIV-1 infection due to its highly vascular structure [45]. There is also evidence in non-human primate models of SIV infection indicating that HIV-1 is present there [19].…”
Section: Model Developmentmentioning
confidence: 99%
“…Tissues were fixed in fresh 4% paraformaldehyde and phosphate-buffered saline and processed as described previously. 8,9 DNA array hybridization and analyses Total RNAs were extracted from snap-frozen spleen tissue homogenized in Trizol (Life Technologies, Carlsbad, CA). Equivalent masses of total RNA were combined from individual macaques to generate pools of RNA from animals with the same disease states.…”
Section: Macaques and Tissuesmentioning
confidence: 99%
“…ISHs were done as described previously, 8,9 except that tissue pretreatments consisted of microwaving in 0.01 M citrate buffer (pH 6.0) followed by acetylation in 0.25% acetic anhydride and 0.1 M triethanolamine and hybridization was done at 50掳C. ISHs simultaneously using sulfur 35 ( 35 S)-labeled and digoxigenin 11-uridine triphosphate-labeled probes were done identically, except that all dithiothreitol (DTT) concentrations were 10 mM.…”
Section: In Situ Hybridizationmentioning
confidence: 99%